Advertising appeals and cultural values in social media brand posts: a comparison between Finland and Spain - Juslin, Elena (My University, 2018)
Social media offers companies new opportunities for marketing and investments in social media marketing are continuously growing. Brands are balancing between standardizing and adapting their traditional media marketing in different countries and often social media brand content is partially made by their global corporate headquarters, thus limiting the possibilities for adaptation of social media content. The purpose of this study is to analyze social media brand posts and compare them in two countries: Finland and Spain. Albers-Miller and Gelb’s framework that combines Pollay’s advertising appeals framework and Hofstede’s cultural dimensions framework is used to create the structure for this study. Content analysis is used as a research method in this study. A mixed method design is applied, as the posts are first categorized into appeals and the differences in frequencies of used appeals is analyzed quantitatively. Then the posts are studied more in-depth qualitatively. Altogether, 480 posts from the most valuable brands in the world were gathered from their Finnish and Spanish Facebook brand pages. The quantitative findings show that only six out of 30 appeals were used to a significantly different extent in Finland and Spain: affiliation, family, distinctive, popular, community and safety. Of those, only the two first were used accordingly with the proposed cultural dimensions. The results show also only some slight qualitative differences in the use of appeals. Some appeals, especially affiliation, were used to take advantage of the opportunities that social media offers as a platform. Thus, few differences in social media marketing of global top brands in Finland and Spain were found.
Keywords: advertising appeals; social media; culture; fi=Master's Degree Programme in International Business|; fi=Digitaalinen media|en=Digital media|